The Role of the National Police in the Misuse of Civilian Weapons Among Civilians - Dwilaksono, Bimo Rizky; Wahyuningsih, Yuliana Yuli (Journal of Law, Politic and Humanities, 2025)
One of the crimes that disturbs the community is crime by using firearms to carry out criminal acts. Recently, this type of crime has been rampant, especially in 2025, where the National Police provided data on 66 cases that occurred at the beginning of this year. On the other hand, the use of weapons is also legalized through licensing procedures. However, this legalization actually creates a situation like a double-edged knife. This is shown by the case of police officer Ferdy Sambo who used his weapon to carry out his murder. Then the case of an ASN in Palembang who used his weapon and he got it illegally. From this, the problem formulations raised from these problems are: 1) how are the mechanisms and requirements for firearms ownership by civilians in terms of Indonesian positive law; and 2) how is the role of the National Police in tackling the misuse of firearms by civilians in terms of firearms ownership procedures. The research method is normative juridical with a statutory, case, and conceptual approach. The results of this study found that the mechanism of ownership and use of firearms is regulated in Chief of Police’s Regulation No. 1/2022 which regulates the mechanism and parties entitled to obtain permission to use weapons. Then, the role of the police starts from providing preventive and repressive legal protection to the community. Preventive protection can be provided from counseling and socialization. Repressive protection can be done by carrying out strong law enforcement against firearms users who cross the line and without going through the licensing process first.